Characteristic of Leaf Area Index of Radish Microgreen Using Image Processing - Empang, Fransiska Cahyani; Sulastri, Ni Nyoman; Budisanjaya, I Putu Gede (Jurnal BETA (Biosistem dan Teknik Pertanian), 2024)
Leaf Area Index (LAI) is a widely used parameter for determining plant biomass, including microgreens. Radish microgreens are a type of microgreens that contain vitamins and polyphenols. This study aimed to obtain LAI values of radish microgreens through image processing and to determine LAI characteristics under combinations of indoor irradiation treatments and seed densities. A Randomized Block Design with two factors was employed to determine the effect of indoor irradiation and seed density on LAI characteristics. Lighting treatments included natural light, UV LED, and Pink LED, while seed densities were 10 g/tray, 12 g/tray, and 14 g/tray. Irradiation was carried out on the second day, and images were taken on the tenth day after sowing. LAI characteristics were determined through image acquisition using a camera and image processing with Python, OpenCV library, and Visual Studio Code. Pearson correlation was used to determine the relationship between LAI values and biomass. Results of the Two-Way ANOVA test showed that the interaction between indoor irradiation treatment and seed density had no significant effect on LAI values (P > 0.05), while indoor irradiation treatment had a significant effect (P < 0.05). The highest LAI values were observed under Pink LED irradiation (0.792–0.985) with thick, wide stems covering almost the entire tray area, while the lowest LAI values were observed under UV LED irradiation (0.426–0.528) with small stems and long, narrow leaves. LAI values positively correlated with microgreen dry biomass (R² = 0.84). In summary, Pink LED irradiation produced the highest LAI values, and LAI strongly positively correlates with microgreen dry biomass.